Pandoraea fibrosis sp. nov., a novel Pandoraea species isolated from clinical respiratory samples - See-Too, Wah Seng; Ambrose, Mark; Malley, Roslyn; Ee, Robson; Mulcahy, Emily; Manche, Emily; Lazenby, James; McEwan, Belinda; Pagnon, Joanne; Chen, Jian Woon; Chan, Kok Gan; Turnbull, Lynne; et al. (Society for General Microbiology, 2019)
Pandoraea species have been isolated from diverse environmental samples and are emerging important respiratory pathogens, particularly in people with cystic fibrosis (CF). In the present study, two bacterial isolates initially recovered from consecutive sputum samples collected from a CF patient and identified as Pandoraea pnomenusa underwent a polyphasic taxonomic analysis. The isolates were found to be Gram-negative, facultative anaerobic motile bacilli and subsequently designated as strains 6399 T (=LMG29626 T =DSM103228 T ) and 7641 (=LMG29627=DSM103229), respectively. Phylogenetic analysis based on 16S rRNA and gyrB gene sequences revealed that 6399 T and 7641 formed a distinct phylogenetic lineage within the genus Pandoraea. Genome sequence comparison analysis indicated that strains 6399 T and 7641 are clonal and share 100 % similarity, however, similarity to other type strains (ANIb 73.2–88.8 %, ANIm 83.5–89.9 % and OrthoANI 83.2– 89.3 %) indicates that 6399 T and 7641 do not belong to any of the reported type species. The major cellular fatty acids of 6399 T were C 16: 0 (32.1 %) C 17: 0 cyclo (18.7 %) and C 18: 1 !7c (14.5 %), while Q-8 was the only respiratory quinone detected. The major polar lipids identified were phosphatidylethanolamine, phosphatidylglycerol and diphosphatidylglycerol. The genomic DNA G+C content of 6399 T was 62.9 (mol%). Strain 6399 T can be differentiated from other members of Pandoraea by the absence of C 19: 0 !8c cyclo and by the presence of C 17: 0 !8c cyclo. Together our data show that the bacterial strains 6399 T and 7641 represent a novel species of the genus Pandoraea, for which the name Pandoraea fibrosis sp. nov. is proposed (type strain 6399 T ). © 2019 IUMS.